Perancangan E-Kinerja Pegawai Kabupaten Bone Bolango Berbasis Android - Hariati Husain; Muh salim; Hamka Witri; Sudirman Panna (JSAI (Journal Scientific and Applied Informatics), 2023)
Improving the performance of civil servants (PNS) is a significant focus for the government, and the evaluation of PNS performance is regulated in government regulations. However, the process of evaluating PNS performance still faces challenges such as manual record-keeping and time-consuming data collection. Therefore, a technology-based system is needed to overcome these issues. The designed E-Kinerja Pegawai (Employee Performance) application is expected to assist PNS in recording and reporting their performance, as well as facilitating the performance evaluation process by the local government. With this system, it is hoped that PNS can focus more on their core duties and functions, while the performance evaluation process becomes faster, more efficient, and well-computerized. This research aims to design an Android-based E-Kinerja Pegawai application in Kabupaten Bone Bolango. The application aims to assist civil servants in recording and reporting their performance and support the local government in evaluating employee performance more efficiently. As the backbone of the government, PNS plays a vital role in serving the community and driving the government machinery in Indonesia. Based on the conducted testing, the obtained V(G) = 3 and Cyclomatic Complexity (CC) = 3. The testing results using test cases demonstrate that the designed system is more effective and efficient.